CADASIL with cord involvement associated with a novel and atypical NOTCH3 mutation. Issue 8 (8th January 2011) - Bentley, Paul; Wang, Tao; Malik, Omar; Nicholas, Richard; Ban, Maria; Sawcer, Stephen; Sharma, Pankaj
Abstract : Background: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is a hereditary cause of cerebral small-vessel disease associated with one of many recognised mutations of the NOTCH3 gene. Spinal cord involvement is not a recognised feature. The authors describe a unique CADASIL pedigree that manifested a stereotypical pattern of cord lesions, in association with a novel and atypical NOTCH3 mutation. Methods: Clinical, radiological, laboratory and genetic characterisation of three affected family members. The associated NOTCH3 mutation was further evaluated by site-directed mutagenesis, immunohistochemistry, CBF1-transcription reporter assay, and screened for in 100 unrelated pathologically confirmed multiple sclerosis (MS) patients. Results: Three members of a family presented with CADASIL caused by a novel NOTCH3 missense mutation, C212Y. Two daughters of the proband also manifested a distinctive pattern of cord lesions confined to the posterocentral zone, cerebral lesions showing both a demyelinating and a typical CADASIL topography, positive antinuclear antibodies and intrathecally derived oligoclonal bands. The mutation occurred in exon 4—that is, outside the Notch3 ligand-binding domain—yet unusually for this location impaired Notch function as assessed by Jagged1 signal transduction. The C212Y mutation did not occur in 100 separate MS cases. Conclusions: This is the first description of an inherited pattern of cord lesions in association with CADASIL. The fact that certain features of dysregulated immunity also occurred, in association with a novel and atypical loss-of-function NOTCH3 mutation, supports evidence for functional interactions of Notch3 with the immune system, in addition to its vascular support role.